THE EFFECT OF RAW MATERIALS INVENTORY, FIXED ASSETS, SHORT-TERM DEBT AND PRODUCTION COSTS ON NET PROFIT PT. ERVIN SUCCESS MUJURINDO - Karen; Thomas Sumarsan Goh; Elidawati; Edison Sagala (Jurnal Ekonomi, 2022)
In the current era of globalization, the business world has developed rapidly, it can be seen the number of new companies that cause the level of competition in the business world is getting higher, one of which is in the field of advertising. Promotion is considered important in the business world. This study aims to determine how the effect of raw material inventories, fixed assets, short-term debt on net profit at PT.Ervin Sukses Mujurindo. This study was conducted using financial statement data of PT. Ervin Sukses Mujurindo. The samples used in this study are raw material inventories, fixed assets, Short-Term Debt, production costs and net income and analyzed using multiple linear regression analysis techniques. The results showed that partially inventories of raw materials, fixed assets and production costs do not affect net income, while short-term debt affects net income. Simultaneously variable inventories of raw materials, fixed assets, short-term debt, and production costs significant effect to net income.